ASSESSING HIV/AIDS KNOWLEDGE RELATED TO SEXUAL BEHAVIOUR AMONG UNDERGRADUATE STUDENTS IN MAKASSAR CITY - Framita Rahman; Sri Wahyuni (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
Since it was first discovered HIV / AIDS has became a very serious global challenge. Indonesia is one of the countries that have a high percentage of people living with HIV / AIDS (PLWHA). A quarter of the total cases of HIV / AIDS in Indonesia are in the adolescences, range of 15-24 years, where most of the undergraduate students (S1) are in this vulnerable age group. Adolescence is a developmental stage that being marked by a great curiosity about the problem of sexuality. This great curiosity is usually not accompanied by adequate knowledge about the issue of sexuality. The purpose of this study was to determine the relationship between knowledge about HIV / AIDS and sexual behavior of undergraduate students in Makassar City. The research method that has been used was cross-sectional, using stratified random sampling method to determine the research sample. There are 536 respondents from 3 universities in Makassar City. The results of this study found that the level of knowledge of students about HIV / AIDS was good at 75.4% (404 respondents) and 24.6% (132 respondents) were poorly informed. Students with no-risk sexual behavior were 346 respondents (64.6%) and 190 respondents were at risk (35.4). Bivariate test results found there was no relationship between knowledge about HIV / AIDS with sexual behavior of undergraduate students with p value 0.155. From this study it can be concluded that knowledge about HIV / AIDS does not affect the sexual behavior of undergraduate students in Makassar City. It is important to look at other factors that might influence undergraduate student sexual behavior.